Review of bean responses to applied fertilizers in Africa - Wortmann, Charles S.; Zake, JYK (Southern Africa Development Coordination Conference (SADCC), 1988)
Results of research work carried out in Africa on the response of beans to NPK fertilizers, liming, S and other secondary/micronutrients, and organic manures are reviewed. Band or spot placement of P, fertilizer management in multiple crop systems, and correlations between soil data, yields, and plant response are also discussed. The frequent response to the residue effect of manure suggests that the benefits may be largely due to the supplying of small amounts of many nutrients. More response to fertilizers can also be expected when management levels are high. The frequent intercropping of beans with other crops complicates the determination of optimal soil fertility management practices; guidelines are therefore needed, possibly based on the needs of the component crops. The lack of information on the feasibility of extrapolating results from one zone to another is highlighted as well as the need for further research on the use of fertilizers and system sustainability on the continent. (CIAT)